The relationship between emotional impulsivity (Urgency), aggression, and symptom dimensions in patients with borderline personality disorder - Sylvia Martin; Jonathan Del Monte; Richard Howard (Borderline Personality Disorder and Emotion Dysregulation)
Abstract Background A hallmark of borderline personality disorder (BPD) is a disposition to anger, irritability and aggression. High impulsivity, particularly high emotional impulsivity (urgency), has been associated with aggression in BPD patients. Aims This study aimed to explore, in a sample of patients with BPD, the subtleties of the relationship between borderline symptomatology, different facets of impulsivity, and an aggressive disposition. Methods Two hundred and twenty patients with a DSM-5 (Sect. 2) diagnosis of BPD were assessed on measures of impulsivity (UPPS model), aggression (Brief Aggression Questionnaire, BAQ-12) and borderline symptoms (Borderline Personality Questionnaire, BPQ). Results Results showed: (i) there was a close relationship between BPD symptomatology and an aggressive predisposition measured by BAQ-12; (ii) emptiness and intense anger were the BPD symptom dimensions most significantly associated with aggression (iii) both negative and positive urgency, and to a lesser extent lack of premeditation and sensation seeking, mediated the relationship between borderline symptom dimensions and aggression. Discussion & conclusion Results suggest a close relationship between almost all dimensions of BPD, but especially anger, and impulsive aggression. They further suggest that urgency, particularly negative urgency, mediates this relationship. Future studies will need to parse aggression into motivationally distinct types.